2016
DOI: 10.1002/jsfa.7823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elicitors on the evolution of grape phenolic compounds during the ripening period

Abstract: The results indicate that the moment of elicitor treatment should be more studied since differences between treated and control grapes were, in general greater several days before harvest in all three varieties. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 44 publications
1
45
0
1
Order By: Relevance
“…Statistically significant differences from the control values were detected for total tannins in skin and seeds from MeJtreated grapes and in wine from both treatments. Gómez-Plaza et al (2017) also found higher concentrations of tannins in Syrah grapes treated with MeJ at harvest. In our study, both treatments (BTH and MeJ) also had an effect on mDP in the skin, seeds and wines.…”
Section: Tannins In Grapes and Winesmentioning
confidence: 70%
See 2 more Smart Citations
“…Statistically significant differences from the control values were detected for total tannins in skin and seeds from MeJtreated grapes and in wine from both treatments. Gómez-Plaza et al (2017) also found higher concentrations of tannins in Syrah grapes treated with MeJ at harvest. In our study, both treatments (BTH and MeJ) also had an effect on mDP in the skin, seeds and wines.…”
Section: Tannins In Grapes and Winesmentioning
confidence: 70%
“…As has been seen, responses to the treatments depended on the variety. Other authors have mentioned a similar dependence on variety: for example, Vitalini et al (2011) in a study of the effect of BTH and chitosan on the melatonin content of grapes, and Gómez-Plaza et al (2017) in a study of the effects of elicitors applied during the ripening period in Syrah, Merlot and Monastrell grapes.…”
Section: Tannins In Grapes and Winesmentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, our results indicate that both elicitor compounds had a clear effect on stilbene compounds, although the effect depended on the grape variety since the application of YD had a positive impact on Grenache and Graciano, whereas MeJ exerted a greater influence on Graciano and Tempranillo. Nonetheless, since the application of YD has also been shown to increase grape stilbenes in Tempranillo in previous years, it could be hypothesized that other external factors such the vintage, or the time between application and harvest, could also influence the effectiveness of the treatments. With regard to the impact of both elicitors, different mechanisms of action can be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Elicitors are able to induce a physiological response in the plant, including activation of the secondary metabolism and synthesis of phenolic compounds through the release of reactive oxygen species (ROS), which stimulate the secondary metabolism pathways and activate antioxidant mechanisms [3]. Recent studies have shown that some elicitors can modify the composition of different grape varieties: in Tempranillo, the application of methyl jasmonate and yeast extracts led to an increase in the concentration of both anthocyanins and stilbenes [4,5]; similar effects were found in Merlot and Monastrell [6]. Further positive effects in the use of elicitors have also been observed in relation to the accumulation of aromas in grapes and wines of the Groppello Gentile cultivars [7], Monastrell [8] and Sangiovese [9].…”
Section: Introductionmentioning
confidence: 96%